The cruelest of all mothers: Marie de l'Incarnation, motherhood, and Christian tradition - Dunn, Mary (Catholic practice in North America, 2016)
Explication : representations of the abandonment in the relations, the letters, and the vie -- Explanation : contextualizing the abandonment within seventeenth-century French family life -- Explanation : the marginalization of motherhood in the Christian tradition -- Explanation : maternal hagiographies and spiritualities of abandonment in seventeenth-century France -- Motherhood refigured : Kristeva, maternal sacrifice, and the imitation of Christ